2019
DOI: 10.1055/a-0887-0205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium‑Vitamin D Co‑Supplementation on Insulin, Insulin Sensitivity, and Glycemia: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to assess the effect of calcium-vitamin D co‑supplementation on insulin, insulin sensitivity, and glycemia. A systematic search was carried out in Web of Science, PubMed, EMBASE, Scopus, and Cochrane library without any language and time restriction up to 12 August 2018, to retrieve the RCTs, which examined the effect of calcium and vitamin D co-supplementation on fasting blood glucose (FBG), insulin, HOMA-B, HOMA-IR, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
8
1
Order By: Relevance
“…The new definition of MAFLD emphasizes on the metabolic disorder among patients with liver steatosis and aims to select patients at high risk of disease progression and to treat patients holistically, therefore the control of metabolic syndrome could be more important than the control of liver injury alone in MAFLD cases. Although the serum 25(OH)D level was not associated with fibrosis in MAFLD in this study, high dose of vitamin D and calcium co-supplementation can significantly reduce FBG and HOMA-IR [30], indicating the beneficial effect of vitamin D supplementation in MAFLD needs further investigation.…”
Section: Discussioncontrasting
confidence: 56%
“…The new definition of MAFLD emphasizes on the metabolic disorder among patients with liver steatosis and aims to select patients at high risk of disease progression and to treat patients holistically, therefore the control of metabolic syndrome could be more important than the control of liver injury alone in MAFLD cases. Although the serum 25(OH)D level was not associated with fibrosis in MAFLD in this study, high dose of vitamin D and calcium co-supplementation can significantly reduce FBG and HOMA-IR [30], indicating the beneficial effect of vitamin D supplementation in MAFLD needs further investigation.…”
Section: Discussioncontrasting
confidence: 56%
“…Data from clinical studies showed that calcium and vitamin D supplementation might exert beneficial effect on glucose metabolism. However, different results have been observed among studies (116,117). The most recent meta-analysis including 12 studies with 4,395 participants in the intervention arm and 4,551 in the control group demonstrated that calcium and vitamin D supplementation significantly reduce fasting glucose, HOMA-IR, and insulin levels (116).…”
Section: Vitamin D and Calciummentioning
confidence: 99%
“…Interestingly, participants with an elevated CRP at baseline (>6.2 mg/L) improved only in the standard dose group. Although it might solely be attributable to chance, Asbaghi et al made a similar observation that higher vitamin D (>2000 IU/day) seemed to have less effect on HOMA‐IR and insulin 41 …”
Section: Discussionmentioning
confidence: 97%